Longitudinal associations between perceived benefits and costs of internet gaming and internet gaming disorder in adolescent gamers: A cross‑lagged structural equation model - Xue Yang; Xin Wang; Miguel Ribeiro Ramos (PLoS ONE, 2026)
This longitudinal panel study aims to investigate the relationships between short/long-term benefits and costs of internet gaming and internet gaming disorder (IGD) in adolescents. First-year high school students with a convenience sampling were recruited from four high schools in central China, and 1032 (56% boys) finished baseline and one-year follow-up surveys. The percentage of IGD was 14.8% at T1 and 13.9% at T2. Cross-lagged structural equation modeling showed that higher levels of IGD symptoms predicted more perceived short- and long-term costs of gaming, while perceptions of short- and long-term costs or benefits did not significantly predict IGD symptoms. These findings suggest experiencing actual negative consequences of internet gaming could enhance perceived costs. Prospective associations between cognitive perceptions and IGD are highlighted and the implications for interventions are discussed.